Beta-lactam antibiotics as reserve medications for the treatment of drug-resistant tuberculosis - G. N. Mozhokina; A. G. Samoilova; I. A. Vasilyeva (Антибиотики и Химиотерапия)
The review article presents an analysis of literature data on the necessity to expand the range of medications possessing anti-tuberculosis activity for the treatment of the most severe forms of drug-resistant tuberculosis through the use of beta-lactam antibiotics in chemotherapy regimens. The mechanism of action of beta- lactam antibiotics on mycobacterium tuberculosis is shown, and the results of in vitro studies to assess their anti-tuberculosis activity are presented. Clinical studies on the use of carbapenems prove the feasibility of their use for the treatment of patients with tuberculosis with multiple and extensive drug resistance of the pathogen.